Lateral Thoughts : Getting the film physics right. (30th March 2020) - Perkowitz, Sidney
Abstract: Whenever bad science appears on screen, a physicist is likely to declare "that's wrong!", making it hard to just sit back and enjoy the action along with your popcorn.